Indonesian MSMEs' Survival Strategies in Facing Global Competition: A Systematic Literature Review - Azzahra, Salwa; Nawawi, Zuhrinal M. (Malacca: Journal of Management and Business Development, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the Indonesian economy. However, this sector is currently facing significant pressure due to increasing global competition. This study aims to analyze and assess the various strategies implemented by MSMEs in Indonesia to maintain their business sustainability in the era of globalization. The study was conducted using a Systematic Literature Review approach to eleven scientific articles published between 2020 and 2025. The results revealed that the main strategies used by MSMEs include utilizing digital marketing, developing innovative products, strengthening business connections, and improving managerial capabilities. These approaches have been proven to support business competitiveness and resilience in an increasingly competitive market. This study provides an important contribution to the development of MSME strategies, both practically and theoretically, and can serve as a reference in formulating MSME-based economic policies in the global era.